2022
DOI: 10.3390/vaccines10071112
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Risk Perception and Hesitancy toward the Booster Dose of COVID-19 Vaccine among People Aged 60 Years and Older in China

Abstract: Background: Given the prevalence of the omicron variant and decreased immunity provided by vaccines, it is imperative to enhance resistance to COVID-19 in the old population. We planned to explore the hesitancy rate toward the booster dose of the COVID-19 vaccine and the association between risk perception and the abovementioned rate among people aged 60 and older. Methods: This national cross-sectional study was conducted in mainland China from 25 May to 8 June 2022, targeting people who were 60 years old or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
45
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 39 publications
6
45
3
Order By: Relevance
“…Concerns about vaccine safety, vaccine efficacy, and lack of confidence were possible underlying causes of vaccine doubt (Vellappally et al, 2022). Vaccine hesitancy became one of the top ten global health threats in 2019, referring to people's reluctance or refusal to be vaccinated, especially among the elderly population (Qin et al, 2022). With the availability of vaccines with proven safety and efficacy, vaccination and non-pharmacological measures had become important resources for managing pandemics and controlling the spread of the virus (Vellappally et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerns about vaccine safety, vaccine efficacy, and lack of confidence were possible underlying causes of vaccine doubt (Vellappally et al, 2022). Vaccine hesitancy became one of the top ten global health threats in 2019, referring to people's reluctance or refusal to be vaccinated, especially among the elderly population (Qin et al, 2022). With the availability of vaccines with proven safety and efficacy, vaccination and non-pharmacological measures had become important resources for managing pandemics and controlling the spread of the virus (Vellappally et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 vaccination was considered a public health intervention that could control the infectious disease (SARS-CoV-2) and reduced the mortality rate (Cao, 2020;Vellappally et al, 2022). Data from the United States, Germany, and South Korea show that COVID-19 vaccination could save most lives and remaining life expectancy (Qin et al, 2022;Vellappally et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, Lewnard and colleagues found that hospital admissions with the Omicron were half of those with the Delta variant ( 17 ). Therefore, doubts have been raised about the necessity of vaccination ( 18 , 19 ). However, the pathogenicity of Omicron might be underestimated due to increased levels of herd immunity via previous infections and vaccinations.…”
Section: Introductionmentioning
confidence: 99%
“…As a country where the virus was first reported, China has received a lot of attention in academia. For example, past literature has discussed mental health issues during the pandemic [ 6 , 7 ], the impact of lockdown policies on different industries [ 8 , 9 ] and vaccination-related issues among various populations [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%